Szolgálok Istenért, egyházért, hazáért - Szűcs, László (Hungary : MTV - Hungarian Television)
Biography of the Hungarian prelate and cardinal of the Roman Catholic Church József Mindszenty (1892-1975).
Keywords: Documentary films